Satın alma ve finansal kiralama yöntemlerinin karşılaştırmalı analizi - Keleş, Hamdi (Fen Bilimleri Enstitüsü, 1994)
Bir malı mülkiyetine sahip olmadan, malikinin rızası ile tasarruf etmeye genel anlamı ile kiralama denmektedir. Kiralama düşünce ve uygulamasının tarihi oldukça eskilere dayanmaktadır. Kâim, esas olarak malın mülkiyetinden değil kullanımından doğması kiralamayı, satın almaya göre rasyonel bir alternatif haline getirmektedir. Modern dünyada kiralama uygulaması, temel olarak iki biçimde ele alınabilir: Faaliyet kiralaması ve finansal kiralama. Faaliyet kiralaması, genellikle kısa vadeli bir sözleşme çerçevesinde temin edilen yatırım malının, teknolojik riske karşı değiştirilmesine imkan tanıyan kiralama türüdür. Finansal kiralama ise kiralayan tarafından kiraya verilmek amacı ile satın alman malın, fiyatını ve fiyatı etkileyen diğer maliyet unsurlanmn tümünü kiracının ödemekle yükümlü olduğu orta vadeli bir kiralama türüdür. Kiralama dönemi sonunda mal, kiracıya sembolik bir bedel karşılığı devredilir. Tez'de kullanılan anahtar kavramlardan biri olan reel yatıran maliyeti, işletmenin yatırım maliyeti ile yatırandan kaynaklanan vergi tasarrufları arasındaki fark olarak tanımlanmaktadır. Banka kredisi ile satm alma tercihinde amortisman ve finansman masrafı, vergi tasarruf etkisi yaratırken yatıran malının satm alınmasında ödenen %15 oranındaki duran varlık KDV'si, likiditasyonu düşük bir aktif olarak önemli finansal yükler taşımaktadır. Finansal kiralamada ise kira ödemeleri vergi tasarruf etkisine neden olmakta buna mukabil kira faturalarının %1'e tabii olması nedeniyle oldukça düşük bir fînans maliyeti doğmaktadır. Tez çerçevesinde geliştirilen simülasyonda miktar ve tarih itibariyle birbirine eşit olduğu varsayılan kredi ve kira ödemeleri halinde yılın ilk yansı finansal kiralama, ikinci yansı banka kredisi ile yatırım yapmak daha anlamlı görülmektedir. Yukandaki varsayım işletme için nakit çıkışlan bağlanımda alternatifler arası kayıtsızlık oluşturarak yöntemlerin vergi tasarrufu potansiyelim ölçmek için kullamlmıştır. Öte yandan 12, 24, 36 ve 48 aylık ödeme planlan için optimum reel yatıran maliyeti koşulu altında veri banka baz kredi maliyetlerine karşılık gelen finansal kiralama baz kredi maliyetlerinin bir dökümü yapılmıştır. Bu analizde de aynı vergi tasarruf etkisine ulaşabilmek için finansal kiralama kredi maliyetlerinin banka maliyetlerine göre daha yüksek olması gerektiği görülmektedir. Diğer bir deyişle kredi maliyeti itibariyle daha yüksek büe olsa kiralama tercih edilebilir. Kaldı ki uygulamada finansal kiralama baz kredi maliyetlerinin banka maliyetlerine göre daha düşük seyrettiği bilinmektedir.

Especially in developed countries, financing the investments by means of leasing is a widely used method as an alternative to direct financing. Leasing takes its legitimacy from the thought that "profit occurs because of using goods rather than getting its possession." In financing by means of leasing; companies can find out sources for their investments by paying only a rent rather than buying machines and equipments in the way of borrowing. Recently, this method has become knowable as international. ELA - European Leasing Association defines the leasing as such; " it is a contract signed for a defined time, between lessor who finds the goods from producer and lessee while lessor owns it, in return, lessee pays rent for using right" There are legal differences between buying and leasing from the view of enterprises: The enterprise,^ the case of the buying, has absolute possession over the goods, changes can be made on machines, he can sell it by breaking up in parts. However, in the case of leasing, lessee should take the permission from the lessor to make some changes on the machine. In other words, even though the possession and using right are together in buying, it is separated into two groups in leasing; possession remains in lessor while using belongs to lessee. Accretion value that is resulted from the using of the machine, belongs to the enterprise both in leasing and buying. Irrational choice of the machines may lead to different results in accordance with the sorts of leasing. In the operational leasing, the machine can be returned back to the lessor, however there is no such a right of lessee in the financial leasing. Because the machine selection is a decision of the enterprise's management, so it is not related to getting machine by means of financial method. In literature, there iş not a concensus about the classification of the types of leasing. We think that it would be better to consider leasing in two parts: 1. Operational Leasing : It is a leasing type in which the goods is leased by a leasing contract for a short term which does not cover the economic life of the relevant goods as regards to the lessee or the lessor. Altough a definite term is mentioned in the contract, the contract may be cancelled or the machine may be changed with a different model with a prior notice. Operational leasing is a short term financial instrument. The lessors in operational leasing are usually the producers of the goods, hi operational leasing,the technological risk pertaining to the machine is borne by the lessor. Therefore, it is a rational alternative to make operational leasing for machines exposed to technogical changes frequently, in stead of buying them. Although a legislation designed for operatinal leasing is not evident in Turkey, this does not mean that operational leasing can not be realised. Indeed, operational leasing is already being made in the framework of present trade relations. Although few in number, there are firms whose business is to lease out their fixed assets and to be in charge of their maintainance during the lease term. 2. Financial Leasing : It is a full payout lease in which the lessee is liable to pay the price of the good bought by the lessor to lease and all the costs affecting the price. As it can be understood from the definition, the main purpose of the financial lessor is to make placements of its funds via machines and to make profit out of these. The selection of the machine belongs to the lessee. At the end of the lease term, the machine is sold to the lessee by a symbolic price. Financial leasing is a medium - term financial instrument. Sale and Lease back, non full payout lease, full payout lease, leveraged lease, specialized lease, cross-border lease, indirect international lease, swap lease, up grade lease joint venture lease,shipped lease, trial period lease and other leasing types are not totally different leasing types, but the derivatives of operational and financial leasing. Sell and lease back which is used in application very often is similar to credit guaranteed by stocks. The reasons for the firms to prefer this method are as follows: XI i - Machine may be owned by a short-term commercial credit. Sel and lease back transforms this short term loan into medium term loan. ii- It makes capitalize the immature depreciation of the investment good. It makes transform the medium term assets into short term assets. Getting the investment goods by means of financial leasing providesmany benefits : 1- Investment goods are the most important goods which produce added value in assets of balance sheet, and the investment cost turns back to enterprise only in medium term period. Rational fund administraticM requires the finance of short term assets by short term resources, medium term assets by medium term resources or by basic capital. It is almost impossible to find medium term capital in our country. Therefore the finance of fixed assets by basic capital will cause lessen of current assets. Financial leasing gives the apportunity of covering the needs such as raw material, effort and half produced goods which are the result of increased capacity due to entrance of machine to production farm. 2. It is observed that the cost of financial leasing based credits are much more less than of the bank's credit our country. 3. The value added tax rate for the goods bought and rent by financial leasing method is 1%. The excemptions of this rule are for fhs automobiles 23% and for commercial vecihles 8%. 15% value added tex should be paid for the machines while buying. 4. In the financial leasing the determined fund cost is not changeable. Neverthless, it is impossible to stabilize the interest rate m the medium term bank credits. 5. Financial leasing payments are registered as expense like general expenditures in accounting. But only the interest payments can be registered as expense in bank credits. This is an important factor for the firm to prefer the financial leasing. 6- Since, Financial Leasing is an off- balanced sheet transaction. It lacks the power to reflect the actual statement of the enterprise. Whereas in developed contries certain regulations have been implemented to prevent this. Industrial xn Enterprises meeting their investment goods through financial leasing, will have an asset structure looking like to those of the commercial enterprises. 7- The method of financial leasing provides more financing capacity compared to the commercial credits. 8- Because the leased goods are contemplated as a quarantee for the lessor firm, mostly there is no need for additional collateral. 9- The firms possessing investment allowance certificate may have a cheaper fund cost by transferring their certificate to the lessor. 10-At the end of the financial leasing contract the ownership of the machine will be transferred by a ceremonial amount. Inspite of those advantages financial leasing has certain obstacles. Because the leased goods are not included in the firm's assets. They cant allocate depreciation and reappraisal. Contracting firms meet with difficulties in providing efficiency certificate, because they can't include the leased machines in their machine park. On the other hand, it may be more profitable to use investment allowance certificate for the firms having high accretion value. The most important contribution of this thesis to the leasing practice of our country, is its simulation to compare bank credits with financial leasing in terms of financing investment goods. Though which instrument the more tax auotfinance can be provided is being searched. The discrepancy between the investment cost and real investment cost. So, the problem is finding the method which provides the minimum cost. According to Turkish Tax Procedural Law, accrual of the cooperation tax is collected in april, July, and October of the following year. So, the time whwn the investment is realized affects the duration to the tax period., and becames important. xm If the investment iş made by means of leasing, it result iin an autofinancing of tax. The part of the lease payments at the rate of corparate income tax remains in the enterprise. Autofinancing made according to repayment times of lease and corparate income tax, is reduced in investment maturity. The reducenert ratio is a discount that makes equal the lease payments to the simulation is the ratio metioned above. Instalment invoices are subject to 1% value added tax (VAT) and this is reducable VAT. The financial pressure of the leasing's VAT to the enterprise, is for a month. The real investment cost of leasing is equal to the differences between the net autofinancing amount of lease payment and the financial pressure of lease's VAT. In the case of financing to the investment by the bank eredir, two kinds of autofinancing sources occur; depreciation and interest payments. On the other side VAT paid at the stage of buying to fixed asset, brings out heavy financial pressure for the enterprises. Because 1/3 of VAT, paid at the rate of 15%, is rounted in following month, 1/3 of it is for the following year and rest is for two years latter. For example, while the enterprise is counting the first instalment, it endures financial cost for a month. Internal rate of return is used for the monthly financial cost. Depreciation is started to be allocated at the year of entrance of machines to the enterprise's asset. In the simulation, it is estimated that the firms are using accelerated depreciation. In accelerated depreciation 50% cost of the machines is allocated for the first year and 25% for the 2nd year, 12,5% for the 3th year and 12,5% for the 4th year. Autofinancing effects is withdrawn to the month in which the investment made, by means of internal rate of return. The loan repayments made to bank chanse in accordance with the base credit cost and maturity. Satisfactory price for a tender can be calculated by going from the base credit cost. Loan repayments occur in two parts as capital and interest payments. As a general rule, the interest payments increases as soon as the credit repayment rises, however the capital repayment decreases. The tax autofinancing effect of interest payment is equal to the rate of corporate income tax. Autofinancing effects occuring because of interest payments is reduced to the investment month by means of leasing's IRR. The net autofinancing amount for a company provided by making an investment with bank credit can be obtained by subtraction the finance cost of value added tax from the total amount of amortization interest xiv payments. Investment cost^an be found by IRR method with reducing the credit payments to their valueson the date which investment was made. In that case, real investment cost is a difference between investment cost and total autofinancing amount. First, the lowest real investment cost has been tried to find in the simulation by the assumption that payments' date and amount are same in both leasing and bank credit. The assumption has been made to determine both methods' structural autofinancing amount. As a result, it is clear that leasing certainly provides tax autofinancing in short term when it is compared to bank credit. Second, Leasing credit cost which is equivalent to the bank credit cost hs been researched under the cancellation condition of the assumption indicated above. The simulation has indicated that the month which the investment is made is very important, For example, if bank credit rate is 80% in a 48 months payment, leasing credit rates which equals real investment cost will be; a- 98.1% ( if investment is made first month) b-92.7%( ' " sixth " ) c-83.7%(" " " " twelfth" ) As a general rule, the rate optimizing the real project cost is bigger than the leasing credit rates which equivalent the bank credit rates. Therefore, it is proven that leasing will be prefered even if it is more expensive, In practice, it is observed that leasing credit rates are lower than bank credit rates despite the structural features of leasing. The companies operated in Turkey should be clasified in three groups; the companies partcipated by banks, special finance instutions and other leasing companies such as the firms specialized on automobil sales. The leasing companies partcipated 80% marked share from the respects of their numbers and transactions volumes. The biggest problem for the leasing companies is to find mid-term credits. Besides their capitals the credit sources of the leasing companies are being credits, morabaha credits of special finance instutions, asset based security (ABS) and bonds and sendication credits found from other countries. However bank credits, bonds and ABS can be found in very xv hard conditions because bank sector collects short term funds and the leasing cost of bonds and ABS are very expensive. If lessee is an international company, sendication credits as a foreign source can not be used. Morabaha credits of finance house has been used very commonly since 1993. In this thesis it is shown that morabaha credits for leasing companies ensure more tax autofinance than those of banks.
The comparison between the methods of finansal leasing and buying by bank credit
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1994
Keywords: Mühendislik Bilimleri; İşletme; Finansal kiralama; Karşılaştırmalı analizs; Satınalma; Engineering Sciences; Business Administration; Financial leasing; Comparative analysis; Purchasing